Forecasting Carbon Dioxide Emissions in Sundarban Islands, India: An ARIMA Model - Mondal, K.; Lal, A. K.; Singh, U. S. (Journal of Scientific Research, 2025)
The Sundarban Islands have suffered greatly due to climate change brought on by greenhouse gas emissions. Carbon dioxide (CO2) is one of the leading emitters that increases the temperature in the atmosphere. Sundarban is one of the largest biospheres in the world facing challenges due to climate change. CO2 plays a crucial role in climate change and that’s why the study on the gas emission in Sundarban is a vital concern. In this article, the CO2 emissions in Indian Sundarban are studied and analyzed from 1980 to 2008 by using ARIMA model. The stationarity test reveals that the nature of the data is I (1) and our study prescribed that the ARIMA (1, 1, 1) is suitable to capture the underlying trend of the emission data. Model’s accuracy tested by the key metrices like Akaike Information Criterion (AIC), RMSE, MAE etc. The proposed model is also utilized for forecasting and its reliable result suggests that the model may be useful in environmental analysis. The findings demonstrate that the CO2 emissions in Sundarban are rising rapidly and putting the region at risk for climatic threats.